2017
DOI: 10.1007/s00592-017-0968-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum 1,5-anhydroglucitol levels slightly increase rather than decrease after a glucose load in subjects with different glucose tolerance status

Abstract: In contrast to the established decline in 1,5-AG levels with long-term hyperglycemia, the present study showed that serum 1,5-AG levels slightly increased by 6-7% after a glucose load. Further studies in different 1,5-AG transport models are needed to investigate the relevant metabolic pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…A Japanese study [ 6 ] of 77 healthy men showed that there were significant increases at 90, 120, and 180 min after the OGTT. Our previous study involving 681 with differing degrees of glucose tolerance suggested that serum 1,5-AG levels slightly increased rather than decreased after a glucose load [ 8 ], which were similar to the results of the present study. A drastic efflux of 1,5-AG into the blood that was induced by acute hyperglycemia may provide a partial explanation to some extent [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A Japanese study [ 6 ] of 77 healthy men showed that there were significant increases at 90, 120, and 180 min after the OGTT. Our previous study involving 681 with differing degrees of glucose tolerance suggested that serum 1,5-AG levels slightly increased rather than decreased after a glucose load [ 8 ], which were similar to the results of the present study. A drastic efflux of 1,5-AG into the blood that was induced by acute hyperglycemia may provide a partial explanation to some extent [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 91%
“…Despite this, only a few studies have attempted to validate agreement between baseline and postload levels of these 3 indicators [ 5 7 ]. Our previous study indicated that serum 1,5-AG levels slightly increased after a glucose load [ 8 ]. Nearly all consistency researches are conducted with the oral glucose tolerance test (OGTT).…”
Section: Introductionmentioning
confidence: 99%
“…A 75-g OGTT was administered to each patient to assay the 2hPG. Standard laboratory measurements were performed 22 . Serum 1,5-AG levels were measured by an enzymatic method (GlycoMark; GlycoMark Inc., New York, NY, USA) on a 7600 autoanalyzer (Hitachi, Tokyo, Japan) with inter- and intra- assay coefficients of variation (CVs) of <3.5% and <2.5%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Glycated hemoglobin A1c (HbA1c) is more easily used as an indicator to detect changes in plasma glucose throughout pregnancy; however, HbA1c is not a substitute for OGTT diagnosis now 12. In recent years, serum 1,5-anhydroglucitol (1,5-AG) has been considered to be a useful glycemic marker for diabetes control and may be a new indicator for detecting GDM 13–15. Serum 1,5-AG reflects shorter-term changes in plasma glucose in patients compared with HbA1c 16.…”
Section: Introductionmentioning
confidence: 99%